2015
DOI: 10.1177/0734242x15615422
|View full text |Cite
|
Sign up to set email alerts
|

Management of waste electrical and electronic equipment in Romania: A mini-review

Abstract: Around the world there are growing concerns for waste electrical and electronic equipment. This is motivated by the harmful effects of waste electrical and electronic equipment on the environment, but also by the perspectives of materials recovery. Differences between countries regarding waste electrical and electronic equipment management are notable in the European Union. Romania is among the countries that have made significant efforts to comply with European Union regulations, but failed reaching the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Some earlier research on the Lithuanian WEEE system (Gurauskienė and Stasiškienė, 2011) also indicated that 28% of consumers store obsolete EEE, the storing period accounting for 10 years on average. In Romania, also a new EU member, some similar trends are observed − 33% of households possess some non-functioning EEE (Ciocoiu et al, 2016). Survey results regarding different handling approaches depending on the size are much in line with other studies.…”
Section: Knowledge and Behaviour Regarding Weeesupporting
confidence: 86%
See 1 more Smart Citation
“…Some earlier research on the Lithuanian WEEE system (Gurauskienė and Stasiškienė, 2011) also indicated that 28% of consumers store obsolete EEE, the storing period accounting for 10 years on average. In Romania, also a new EU member, some similar trends are observed − 33% of households possess some non-functioning EEE (Ciocoiu et al, 2016). Survey results regarding different handling approaches depending on the size are much in line with other studies.…”
Section: Knowledge and Behaviour Regarding Weeesupporting
confidence: 86%
“…A lack of collection points as an obstacle of proper WEEE recycling was also acknowledged by Botelho et al (2016) with some 60% of respondents in the case of Portugal. Therefore, according to some authors, promotion of the take-back programmes (Ciocoiu et al, 2016) or/and expansion of take-back channel variety and improvement of the existing ones (Friege et al, 2015) could be the options to increase WEEE collection rates.…”
Section: Knowledge and Behaviour Regarding Weeementioning
confidence: 99%
“…There are over 2,000 collection points in commercial networks in Romania, with adequate infrastructure for weekly or monthly collection (Pacesila et al, 2016). However, the necessary of municipal ewaste collection points are less than the number of authorized collectors in most of the Romanian counties (Ciocoiu et al, 2016).…”
Section: E-waste Collection In Urban Areasmentioning
confidence: 99%
“…The Directive 2012/19/EU of the European Parliament and of the Council of 4 July 2012 on WEEE [132] adapted for Romania requires a WEEE collection of minimum of 40% of the existing market amount until 2020 and 85% of the generated waste by 2021. Still, the waste recycling management strategy is progressing slowly due to the lack of proper infrastructure for WEEE recycling with a low number of collection centers and only few national programs for waste recycling, and population ignorance regarding the negative effects on the environment [133][134][135].…”
Section: Short Overview Of Weee Recycling In Romaniamentioning
confidence: 99%